2019
DOI: 10.1002/nau.24006
|View full text |Cite
|
Sign up to set email alerts
|

Role of β‐3 adrenergic receptor polymorphism in overactive bladder

Abstract: Aims Women with overactive bladder (OAB) have a higher frequency of a single‐nucleotide polymorphism (SNP) at codon 64 of the β‐3 adrenergic receptor gene (ADRB3). Since the SNP results in an amino acid substitution that could theoretically alter receptor protein function, we hypothesized that those with the SNP would display greater OAB symptom severity. Therefore we aimed to compare OAB severity between women with this SNP and women with the wild type genotype. Methods A retrospective cohort study was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…26 In another newly published study, 303 women (predominantly non-Hispanic, Caucasian population) with OAB were investigated for the Trp64Arg polymorphism, 83.8% were found as wild-type and 16.2% heterozygous. 27 That means that the wild-type (T) and variant allele (C) of Trp64Arg polymorphism frequency was 91.9% and 8.1%, respectively. No relationship was found In the present study, we compared the frequency distribution of Trp64Arg polymorphism in OAB patients and non-OAB controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In another newly published study, 303 women (predominantly non-Hispanic, Caucasian population) with OAB were investigated for the Trp64Arg polymorphism, 83.8% were found as wild-type and 16.2% heterozygous. 27 That means that the wild-type (T) and variant allele (C) of Trp64Arg polymorphism frequency was 91.9% and 8.1%, respectively. No relationship was found In the present study, we compared the frequency distribution of Trp64Arg polymorphism in OAB patients and non-OAB controls.…”
Section: Discussionmentioning
confidence: 99%
“…Another recently published study showed also that ADRB3 polymorphism is not associated with the clinic of OAB patients of Turkish ancestry 26 . In another newly published study, 303 women (predominantly non‐Hispanic, Caucasian population) with OAB were investigated for the Trp64Arg polymorphism, 83.8% were found as wild‐type and 16.2% heterozygous 27 . That means that the wild‐type (T) and variant allele (C) of Trp64Arg polymorphism frequency was 91.9% and 8.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although several factors seem to be involved in the mechanisms underlying OAB, present studies may suggest that dysfunction of beta3-AR resulting from its gene polymorphism, at least partially, conduces to the pathophysiology underlying OAB ( Yamaguchi, 2002 ; Yamaguchi and Chapple, 2007 ; Peyronnet et al, 2019 ). Therefore, Trp64Arg polymorphism of ADRB3 , leading to a missense mutation and altering receptor function, would be speculated on increased susceptibility to OAB ( Ferreira et al, 2011 ; Meekins et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of families and twins have suggested a genetic predisposition to OAB ( Rohr et al, 2004 ; Wennberg et al, 2011 ). Trp64Arg polymorphism (ID rs4994) of ADRB3 leads to a missense mutation resulting in an amino acid change from tryptophan to arginine and altering receptor function, which has been proposed as a pathophysiologic mechanism for OAB ( Michel and Korstanje, 2016 ; Meekins et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation